Guidance system supporting design phase - Din, Jamilah; Idris, Sufian; Mohd Noah, Shahrul Azman (Malaysian Educational Technology Association, 2007)
The available literature supports the fact that some students experience difficulty learning about object-oriented design (OOD) principles. Many object-oriented development methods and object-oriented CASE tools have been emphasized on how to develop semantically correct object-oriented models. However, a correct model does not mean that the design is flexible and reusable. A correct model needs to comply with the object-oriented design principles, design heuristics, and design patterns. Helping students make good design is important because the design will influence the implementation and maintenance effort later. There are limited CASE tools that are able to guide the student (user) during the design process by providing intelligent assistance in the form of advice, and suggesting alternative solutions by monitoring the design process. Contemporary CASE tools although have excellent facilities for drawing, editing and maintenance of software specifications, they lack in the sense of ‘guiding’ users to a better design and do not possess what considered as ‘knowledge-intensive’ driven to design. This paper proposes a guidance system which guides the student in learning object-oriented designs. This guidance system will let the student carry out the design tasks while the system look at the corresponding heuristic catalogues. It will notify the student with a message regarding the heuristics it has identified and give suggestion how to correct it. This guidance system not only assists the design process but also upgrades student’s knowledge. Techniques used in guiding student such as tutoring system, coaching system and critiquing system are also compared and discussed in this paper.